2015
DOI: 10.1016/j.physbeh.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The physiological consequences of crib-biting in horses in response to an ACTH challenge test

Abstract: • The function of stereotypic behavior (crib-biting) is not clear.• We used an ACTH challenge test to test the coping hypothesis of stereotypies.• We compared adrenal and sympathetic responses of stereotypic and control horses.• We found higher cortisol responses in the stereotypic group compared to controls.• Our results suggest that crib-biting is a coping strategy serving to reduce stress. a b s t r a c t a r t i c l e i n f o Stereotypies are repetitive and relatively invariant patterns of behavior, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 44 publications
0
18
1
Order By: Relevance
“…Because proactive animals act to exert control over their environment, they might be more prone to form routines and, by extension, to fall into stereotypies (7). This hypothesis, however, has not been supported by the physiological results of our previous study, which revealed higher HPA-axis reactivity in stereotyped (crib-biters) compared to control horses, which is more characteristic of reactive individuals than proactive ones (28). In sum, the issue of whether stereotypic behavior can be linked to individual differences, and particularly coping styles in response to chronic stress, has not been resolved.…”
Section: Introductioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Because proactive animals act to exert control over their environment, they might be more prone to form routines and, by extension, to fall into stereotypies (7). This hypothesis, however, has not been supported by the physiological results of our previous study, which revealed higher HPA-axis reactivity in stereotyped (crib-biters) compared to control horses, which is more characteristic of reactive individuals than proactive ones (28). In sum, the issue of whether stereotypic behavior can be linked to individual differences, and particularly coping styles in response to chronic stress, has not been resolved.…”
Section: Introductioncontrasting
confidence: 69%
“…The control group was made up of horses that had never been observed crib-biting or performing other stereotypies by their owners [i.e., weaving, box walking, head tossing nodding (38)]. This grouping was verified later on during the first study (28) and during this study (i.e., crib-biters were all observed crib biting, while control horses were not seen displaying any stereotypy). For each crib-biting horse, we tried to find a control horse that was of similar breed, sex and age, and that was housed in the same conditions (i.e., if possible, on the same farm, Table 1).…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…Different approaches including the assessment of behavioral (Bachmann et al, 2003;Rietmann et al, 2004), autonomic nervous system (Bachmann et al, 2003;Rietmann et al, 2004) and neuroendocrine reactions (Alexander and Irvine, 1998;Briefer Freymond et al, 2015), specifically regarding the hypothalamic pituitary adrenal (HPA) axis, have been used to determine stress responses in horses. The HPA-axis plays a critical role in chronic stress (Mormède et al, 2007) and has broad and long-lasting effects on the body (Moberg and Mench, 2000).…”
Section: Introductionmentioning
confidence: 99%